If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.1 = 3y + 11.6 Reorder the terms: 1.1 = 11.6 + 3y Solving 1.1 = 11.6 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 1.1 + -3y = 11.6 + 3y + -3y Combine like terms: 3y + -3y = 0 1.1 + -3y = 11.6 + 0 1.1 + -3y = 11.6 Add '-1.1' to each side of the equation. 1.1 + -1.1 + -3y = 11.6 + -1.1 Combine like terms: 1.1 + -1.1 = 0.0 0.0 + -3y = 11.6 + -1.1 -3y = 11.6 + -1.1 Combine like terms: 11.6 + -1.1 = 10.5 -3y = 10.5 Divide each side by '-3'. y = -3.5 Simplifying y = -3.5
| 3x-1.5=2(3x+6) | | 7x+3x^2= | | 3x+2(3x+5)= | | 1.8=0.7u+0.1u | | a=3a-36 | | 3-3x=4x-4x | | 4n+3=3 | | 4t-41=3t-20 | | (x)(5/4)/2=100 | | 8u-52=3u-2 | | (x)(5/4)/2=10 | | 2s+50=5s-13 | | 3x/11-9/11=-3/11 | | -20=-8x+5(x-7) | | -5/6x15 | | 2x-1=-2x+31 | | x=6.5+0.5y | | 3-3i/4i | | 1502x=195-1x | | (2x)^3/4x^2 | | 5w+5=40 | | X=16/cos(64) | | 3(r-16)=9 | | 5x+90=200 | | (2x-2)+(x+1)-x-(x+1)=(2x-9)+(x+1)+(x+8)+x | | [3(7-5)]/2 | | 3(1/3)-1 | | 2x/3-x-1/2 | | 2g+6-5=11 | | 0.4=40/100 | | x*2/3=11/12 | | 6=2-3f-5+5f |